2021
DOI: 10.1002/bio.4045
|View full text |Cite
|
Sign up to set email alerts
|

pH‐responsive zwitterionic carbon dots for detection of rituximab antibody

Abstract: Zwitterionic carbon dots (CDs) have received much attention as a result of good photostability, high biocompatibility, and high quantum yield. In this study, novel zwitterionic CDs were synthesized using a simple hydrothermal method of citric acid (CA) and l‐histidine as carbon and nitrogen precursors, respectively. Prepared zwitterionic CDs have an average particle size of 4 nm diameter and showed green fluorescence with a peak at 530 nm when excited at 470 nm; quantum efficiency was 39.34% using rhodamine 6G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The UV absorption peak of the CDs was located at 280 nm, which was attributed to the n-p* transition of the C]O group. 32 On the basis of the IR and UV results, it was concluded that the CDs contained carbonyl or conjugated carbonyl groups (Fig. 4c).…”
Section: Characterization Of the Cdsmentioning
confidence: 96%
“…The UV absorption peak of the CDs was located at 280 nm, which was attributed to the n-p* transition of the C]O group. 32 On the basis of the IR and UV results, it was concluded that the CDs contained carbonyl or conjugated carbonyl groups (Fig. 4c).…”
Section: Characterization Of the Cdsmentioning
confidence: 96%
“…[ 20 ] In fact, the precursors of copper nanoclusters (CuNCs) are inexpensive and more readily available than those for synthesizing gold nanoclusters (AuNCs) and silver nanoclusters (AgNCs). Furthermore, carbon dots (CDs) are used as high‐performance fluorescent nanoprobes in various fields such as chemical sensing [ 21–23 ] and bioimaging applications [ 24,25 ] due to their properties of good water‐solubility, low cost, easily synthesis and outstanding optical properties. These properties make them promising applications for ratiometric fluorescent probes.…”
Section: Introductionmentioning
confidence: 99%
“…analysis using CDs is a promising platform for chemical, biological, and environmental detection with high sensitivity and selectivity. [25][26][27] However, the development of suitable CDs for bilirubin detection has not been explored in depth. Anjana et al [28] have reported an effective fluorescence probe for the detection of bilirubin using sulfur (S)and nitrogen (N)-doped CDs, which were synthesized using citric acid and L-cysteine by a microwave-assisted method.…”
mentioning
confidence: 99%